Books are bridges - Bündge, Hendrik 1982-; Andreasen, Kasper 1979-; Pütz, Uta 1969- (backbonebooks, 2021)
How can we still find ways to connect with each other? Can books play a role in this connection? And from where to where can they take us? For the show in A — Z presents, I’ve come up with a strategy to bring people and ideas together. A participative, open, non-ending work that could exist in the space, but that couldn’t exist without a form of contact. A book that will construct itself throughout the duration of the show. The thickness, amount of pages, and content won’t depend on me but on the public. A book that functions as a bridge that connects people, ideas, ... http://backbonebooks.net/books-are-bridges/
In Schachtel
Das Buch entstand während und anlässlich der Ausstellung "Books are bridges" (A-Z presents, Berlin)
"The answers to the sentence "Books are bridges between _ and _" that were sent back or filled out during the exhibition, are contained in this book."
Keywords: Künstlerbuch